Specimen size effects on direct shear test of silty sands. Issue 2 (15th March 2017) - Ziaie Moayed, Reza; Alibolandi, Mahdi; Alizadeh, Amir
Abstract : The main objective of this study is to investigate the effect of the scale factor on the shear strength of sands with different silt contents. For this purpose, the samples of Firouzkooh sand with 0, 10, 20 and 30% silts percentages are prepared at their maximum dry densities with corresponding optimum moisture content (Silt percentages are by weight). Direct shear tests are performed with three different shear box sizes (60 × 60, 100 × 100 and 300 × 300 mm). Results indicate that the peak shear strength and the peak friction angle decreases with increasing the shear box size while residual shear strength is constant. Also increasing the silt percentages caused a decrease in the peak shear strength. The results show that the reduction rate in friction angle decreases with increasing the box sizes and increasing the silt content.